LOW COST RFID-BASED SECURITY SYSTEM FOR PARKING LOTS - Mia Galina; Muhammad Hanief; Luthfil Hadi Nugroho (Universitas Nusa Cendana, 2022)
The rapid advancement of technology is reflected in improvements to equipment that facilitate human work, such as the parking system employing RFID (Radio Frequency Identification). The RFID technology is able to record incoming and outgoing data for short-distance data transfer. The intended audience for this work's development is junior or senior high school students. Finally, students are expected to be able to develop effective parking solutions with little cost and expertise. Two registered cards and one unregistered card are used to test this tool, with ten tests being run on each card. Some of the tests that have been carried out include the efficiency of RFID and ultrasonic sensors in reading registered cards and detecting heading vehicles, as well as the use of RFID obstacles to test the extent to which the frequencies in RFID can operate, even when they are still obstructed by other objects. The test results show that the system could work properly, and read with the right level of precision with 0.3 seconds an average delay. Additionally, the resulting RFID reader can still detect registered cards at a distance of 1.5 cm even with a border thickness of up to 2.0 mm.